Towards a cost-efficient & standardised monitoring protocol for subtidal reef fish in the Agulhas ecoregion of South Africa,Towards a cost-efficient & standardised monitoring protocol for sub-tidal reef fish in the Agulhas eco-region of South Africa - Bernard, Anthony Thomas Firth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
Under the growing demand for marine fish resources, and the apparent and expected impacts of global climate change, there is a need to conduct long-term monitoring (LTM) to ensure effective management of resources and conservation of biodiversity. However LTM programmes often suffer from design deficiencies and fail to achieve their objectives. These deficiencies stem from the fact that insufficient consideration is afforded to the design phase, with programmes selecting methods that are not suitable to address the objectives, or are not cost-efficient, compromising the sustainability of the LTM. To facilitate the establishment of LTM programmes along the southern coast of South Africa, background research needed to be conducted to identify which methods were most appropriate for LTM of reef fish. This study presents a detailed field-based assessment of the suitability and cost-efficiency of monitoring methods for long-term monitoring of reef fish in the Agulhas Ecoregion of South Africa. The approach adopted to identify the method, or suite of methods most suited for LTM, involved (i) the selection of methods considered suitable for LTM, (ii) the individual assessment and optimisation of method performance, and (iii) the comparative assessment of the fish community sampled by the different methods. The most suited method(s) were then identified as those that provide the most comprehensive assessment of the fish community and had the highest cost-efficiency. The research was conducted between January 2008 and 2011 in the Tsitsikamma and Table Mountain National Park (TNP and TMNP, respectively) marine protected areas (MPAs) within the Agulhas Ecoregion. The methods selected included fish traps (FT), controlled angling (CA), underwater visual census (UVC), remote underwater video (RUV), baited RUV (BRUV) and remotely operated vehicles (ROV). The individual assessment and optimisation was conducted with the FT, UVC, RUV and BRUV methods. The assessment of the FT method aimed to identify the optimal soak time, and whether or not the size of the funnel entrance to the trap affected the catch. The results identified that larger funnel entrances caught more fish and soak times of 80 minutes produced the highest catches per unit effort. However the data were highly variable and the method detected few of the species typical of the region. Fish traps were also associated with high levels of mortality of fish post-release. The assessment of UVC strip transect method involved directly comparing the precision of data collected by researchers and volunteers using a novel double-observer technique (paired-transects). The results showed considerable error in both the volunteers and researchers data, however the researchers produced significantly higher precision data, compared to the volunteers. The distinction between researchers and volunteers was not evident in the data for the dominant species of fish. For all observers, the abundance of a species in the sample had a significant influence on its detectability, with locally scarce or rare species poorly detected. UVC was able to sample the majority of species typical of reefs in the region, however it appeared plagued by observer and detectability biases. The assessments of RUV and BRUV were conducted simultaneously which enabled the assessment of the effect of bait on the observed fish community. In addition the optimal deployment time for both methods to maximise species richness and abundance was determined. The results showed that BRUV, and to a lesser degree RUV, were able to effectively survey the reef fish community for the region with a 50 minute and 35 minute deployment time, respectively. Baited remote underwater video was especially good at detecting the invertebrate and generalist carnivores, and cartilaginous species. On the other hand, RUV was more effective at surveying the microinvertebrate carnivores. Remote underwater video was characterised by higher data variability, compared to BRUV, and was ultimately considered a less cost-efficient monitoring method. Comparative methods assessments were conducted during two field experiments with the FT, UVC and BRUV methods in the TMNP MPA, and the FT, CA, UVC, RUV, BRUV and ROV methods compared in the TNP MPA. The objectives of the comparison were to investigate differences in the fish communities observed with the different methods, and to determine the power of the data to detect an annual 10% growth in the fish populations over a period of five years. The results from the method comparison were in turn used to conduct the cost-benefit analysis to determine the efficiency of the different methods at achieving monitoring objectives requiring population data from multiple trophic and functional groups with the community, and from species of fisheries importance. The results indicated that FT, CA and ROV were ineffective at monitoring the reef fish community, although CA appeared to provide valuable data for the dominant fisheries species. Both CA and FT required minimal initial investment however, the variability in the data translated into high annual monitoring costs, as the required sampling effort was great. The ROV required the highest initial investment and was identified as the least cost-efficient method. Underwater visual census was able to adequately survey the bony fish within the community, however it did not detect the cartilaginous species. Underwater visual census required a large initial investment and was not cost-efficient, as a many samples were required to account for the variability in the data. Remote underwater video provided a comprehensive assessment of the reef fish community, however it too was associated with high levels of variability in the data, compared to BRUV, reducing its cost-efficiency. BRUV provided the most comprehensive assessment of the reef fish community and was associated with the highest cost-efficiency to address the community and fisheries species monitoring objectives. During the course of this research stereo-BRUV has gained considerable support as an effective reef fish monitoring method. Although not tested during this research, stereo-BRUV is preferred to BRUV as it provides accurate data on the size of fish. However, the initial investment of stereo-BRUV is over three times that required for the BRUV. Although it is recommended that a baited video technique be used for LTM in the Agulhas Ecoregion, the choice between BRUV and stereo-BRUV will depend on the specific objectives of the programme and the available budget at the implementing agency.
Keywords: Reef fishes -- South Africa; Reef fishes -- Monitoring--South Africa; Fish stock assessment -- South Africa; Coastal zone management -- South Africa; Fish communities -- South Africa; Marine parks and reserves -- South Africa; Marine resources conservation -- South Africa; Marine biodiversity conservation -- South Africa